Analisis Sistem Mukhabarah Pada Usaha Tani Padi Di Desa Huraba Kecamatan Marancar Kabupaten Tapanuli Selatan - Nur Azizah Siregar; Tuti Anggraini; Tri Inda Fadhila Rahma (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2024)
Abstract How is the mukhabarah system on farming in Huraba village, Marancar sub-district, South Tapanuli regency and how it impacts on the welfare of community farmers in Huraba village, especially rice farming, is the purpose of this research. With Descriptive Qualitative method, which is an investigation that underlines understanding in one problem. Observation and interviews as information gathering. Primary sources in the form of sentence expressions spoken by informants, namely 5 tenants and 5 landowners and secondary data obtained through literature review used as material for analysis. The results obtained from this study are that the mukhabarah contract carried out in Huraba Village, Marancar Subdistrict is not suitable when viewed from muamalah fiqh because in this mukhabarah contract, regardless of the harvest obtained, the landowner's share remains the right of the landowner without deducting the cost of cultivation, this contract has a positive impact because it helps landowners who do not have time to work and the cultivator also feels helped economically, thus making agriculture in Huraba Village continue to be productive. Keywords: Akad Mukhabarah; Fikih Muamalah; Farming Business; Welfare Abstrak Bagimana sistem mukhabarah pada usaha tani didesa Huraba Kecamatan Marancar Kabupaten Tapanuli Selatan serta bagaimana dampaknya terhadap kesejahteraan petani masyarakat di desa Huraba khususnya usaha tani padi menjadi tujuan penelitian ini. Dengan metode Kualitatif Deskriptif, yakni investigasi yang menggarisbawahi pemahaman dalam satu masalah. Observasi dan wawancara sebagai pengumpulan informasi. Sumber primer dalam bentuk ungkapan kalimat yang diucapkan oleh para informan, yaitu 5 orang penggarap dan 5 orang pemilik lahan dan data sekunder yang diperoleh melalui kajian literatur yang digunakan sebagai bahan analisis. Hasil yang diperoleh dari penelitian ini adalah bahwa akad mukhabarah yang dilakukan di Desa Huraba Kecamatan Marancar kurang sesuai jika ditinjau dari fikih muamalah karena dalam akad mukhabarah ini, berapapun hasil panen yang diperoleh, bagian pemilik lahan tetap menjadi hak pemilik lahan tanpa dikurangi dengan biaya penggarapan, akad ini berdampak positif karena membantu sipemilik tanah yang tidak mempunyai waktu untuk menggarap dan si penggarap juga merasa terbantu perekonomiannya, sehingga menjadikan pertanian di Desa Huraba terus produktif. Kata Kunci: Akad Mukhabarah; Fikih Muamalah; Usaha Tani; Kesejahteraan